Insomnia in Hemodialysis Patients with Functional Disability - Kurniawaty, Heni; Widyawati, Ika Yuni; Qona’ah, Arina (International Journal of Psychosocial Rehabilitation, 2020)
Chronic kidney disease with hemodialysis therapy can cause insomnia or sleep disturbances both in terms of quality and quantity of sleep. The impacts of insomnia itself was the occurrence of functional disability and worsen it. The purpose of this research was to analyze the relationship between insomnia and functional disability in CKD patients undergoing hemodialysis in the hospital. A correlational study with cross-sectional design was used in this study. There are 128 respondents involved in this study who were selected using simple random sampling. The variables were insomnia and functional disability which were measured using the Pittsburgh Quality Sleep Index (PSQI) and Functional Independence Measure (FIM) questionnaire. Chi-square analysis with significance level